Placenta Accreta Spectrum Disorders - The Impact of the Creation of a Multidisciplinary Team on Maternal Outcomes in Portugal - Beatriz Teixeira; Pedro Viana Pinto; Rodrigo Realista; Manuela Silva; Antónia Costa; Ana Paula Machado; Marina Moucho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective To describe a cohort of placenta accreta spectrum (PAS) cases from a tertiary care institution and compare the maternal outcomes before and after the creation of a multidisciplinary team (MDT). Methods Retrospective study using hospital databases. Identification of PAS cases with pathological confirmation between 2010 and 2021. Division in two groups: standard care (SC) group - 2010-2014; and MDT group - 2015-2021. Descriptive analysis of their characteristics and maternal outcomes. Results During the study period, there were 53 cases of PAS (24 - SC group; 29 - MDT group). Standard care group: 1 placenta increta and 3 percreta; 12.5% (3/24) had antenatal suspicion; 4 cases had a peripartum hysterectomy - one planned due to antenatal suspicion of PAS; 3 due to postpartum hemorrhage. Mean estimated blood loss (EBL) was 2,469 mL; transfusion of packed red blood cells (PRBC) in 25% (6/24) - median 7.5 units. Multidisciplinary team group: 4 cases of placenta increta and 3 percreta. The rate of antenatal suspicion was 24.1% (7/29); 9 hysterectomies were performed, 7 planned due to antenatal suspicion of PAS, 1 after intrapartum diagnosis of PAS and 1 after uterine rupture following a second trimester termination of pregnancy. The mean EBL was 1,250 mL, with transfusion of PRBC in 37.9% (11/29) - median 2 units. Conclusion After the creation of the MDT, there was a reduction in the mean EBL and in the median number of PRBC units transfused, despite the higher number of invasive PAS disorders.